'We disputed every word': how Kyrgyzstan's moderates tame ethnic nationalism. Issue 2 (19th February 2016) - Marat, Erica
Abstract: In post‐violence Kyrgyzstan, a small group of civic‐minded nationalists are fighting to tame extremist voices by formulating their own reconciliation policies. These moderates have adopted several strategies, including persuasion and bargaining with nationalistic elites. This process is not without its limitations. Important issues, such as forging a civic identity for the majority ethnic group, remain unaddressed. Still, moderates' policy achievements and concrete actions are likely to continue to undercut nationalist rhetoric. The case of Kyrgyzstan offers one possible alternative to the Soviet paradigm of framing nationhood alongside citizenship.